1977
DOI: 10.1038/bjc.1977.38
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for acute myelogenous leukaemia: a controlled clinical study 2 1/2 years after entry of the last patient

Abstract: Summary.-One hundred and thirty-nine untreated patients with acute myelogenous leukaemia (AML) were admitted between August 1970 and December 1973 and allocated into two remission treatment regimens: one to receive chemotherapy alone and the other chemotherapy with immunotherapy. Of the patients who attained remission, 22 were in the chemotherapy group and in September 1975 2 remained alive, the median survival time being 270 days and after relapse 75 days. Twenty-eight patients received immunotherapy during r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

1978
1978
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…Criteria for the diagnosis of acute myelogenous leukemia and therapeutic protocols used have been reported in detail elsewhere (9,10). All the patients studied were in complete remission and received either chemoinimunotherapy with BCG plus irradiated allogeneic leukemic myeloblasts according to the protocol reported by Powles et al (11,12) or the same chemotherapy plus BCG alone (2). The leukemic myeloblasts were removed from patients at the time of diagnosis, using the IBM Blood Cell Separator (IBM Corp., White Plains, N.Y.) (13) and then frozen in liquid nitrogen using techniques reported elsewhere (14).…”
Section: Methodsmentioning
confidence: 99%
“…Criteria for the diagnosis of acute myelogenous leukemia and therapeutic protocols used have been reported in detail elsewhere (9,10). All the patients studied were in complete remission and received either chemoinimunotherapy with BCG plus irradiated allogeneic leukemic myeloblasts according to the protocol reported by Powles et al (11,12) or the same chemotherapy plus BCG alone (2). The leukemic myeloblasts were removed from patients at the time of diagnosis, using the IBM Blood Cell Separator (IBM Corp., White Plains, N.Y.) (13) and then frozen in liquid nitrogen using techniques reported elsewhere (14).…”
Section: Methodsmentioning
confidence: 99%
“…We found that second remissions were the rule (6/7 patients), while third and subsequent remissions commonly occurred (Freeman et al, 1973), in contrast to the general experience that relativelv few patients achieved second remission in adult AML (Wiernik and Serpick, 1970;Bailey et al, 1971;Crowther et al, 1973;Powles, 1973;Powles et al, 1973Powles et al, , 1977. There are few reports of third remissions (Whittaker and Slater, 1977 examination was repeated within 2 weeks.…”
mentioning
confidence: 53%
“…C = 5-day course of Arc C + Thioguanine and A alternating monthly, except that dosage of thioguanine was 2-0 mg/kg (laily orally (Barts chemotherapy maintenance). I= 109 irradiated allogeneic leukaemic cells plus 106 Glaxo BCG (Freeman et al, 1973 Immunotherapy appears to prolong first remission Powles et al, 1977), facilitate reinduction (Freeman et al, 1973) and lengthen postrelapse survival (Powles et al, 1977 …”
Section: Resultsmentioning
confidence: 99%
“…More than 20 years ago, some patients with AML received pooled, irradiated allogeneic leukemic cells in order to enhance their immune system. 109 At present, donor lymphocyte infusions (DLI) following allogeneic stem cell transplantation is the treatment of choice for relapse in chronic and acute myeloid leukemia. 110 Unfortunately, DLI is less successful in the treatment of AML patients.…”
Section: Potential Therapy With Leukemia-derived Dcsmentioning
confidence: 99%